Jaminan Perorangan (Personal Guarantee) Dalam Perkara Kepailitan Perseroan Terbatas - Semboeng, Jessica Vallencia; Maramis, Ronny A.; Kalalo, Merry E. (Innovative: Journal Of Social Science Research, 2024)
Debt coverage that is tied to an individual guarantee agreement for the debtor to obtain credit is a common thing in banking, especially when the debtor is a company. However, in the process of repaying loans, namely paying or paying off debts, problems often occur when not being able to pay credit, resulting in bad credit. Usually banks as creditors provide credit rescue efforts or result in the execution of collateral or guarantees. However, for debtors who have a lot of credit debt and are unable to pay it anymore and it is due to be collected, there is a request for a postponement of debt payment obligations or a request for a bankruptcy statement to the Commercial Court in the General Courts in accordance with Law Number 37 of 2004 concerning Bankruptcy and Postponement of Payment Obligations Debt. The guarantor as a third party who binds himself and has waived his special rights as regulated in the Civil Code must take responsibility according to the clauses agreed in the agreement. Thus, the guarantor must be responsible for the guaranteed debt of the debtor, and can even replace the debtor's position completely.